Etno Design: Innovation in Science and Mathematics Learning Based on Local Wisdom - Wibawa, I Made Citra; Ni Putu Sri Ratna Dewi; Ketut Sedana Arta (MIMBAR PGSD Undiksha, 2024)
There are still many students who have difficulty in understanding the concepts of Science and Mathematics because of the learning approach that is not contextual and irrelevant to the surrounding environment. The lack of learning media that relates the material to local wisdom is also an obstacle in improving student understanding. This research aims to develop Ethno Design, which is an innovative and contextual learning model of Science and Mathematics based on local wisdom. This type of research is Research and Development (R&D) using the ADDIE development model. The research subjects consisted of 2 material experts, 2 media experts, and 2 learning experts. The trial was carried out involving 1 teacher/practitioner, 3 students (individual trial), and 6 students (small group trial). The data collection method uses observation, interviews, questionnaires, and tests, with instruments in the form of questionnaires and test questions. The data analysis techniques used are qualitative descriptive analysis, quantitative descriptive analysis, and inferential statistics. The results showed that the assessment of material experts was 94% (very valid), media experts 91% (very valid), and learning experts 93% (very valid). The individual trial obtained a score of 95% (very practical), the small group trial 96% (very practical), and the teacher's assessment reached 92% (very practical). The results of the effectiveness test showed an increase in student learning outcomes after the implementation of the Ethno Design model.